A Preyssler-type polyoxometalate-based coordination supramolecule with proton conducting property. (1st September 2019) - Sun, Sai; Zhu, Li-Jie; Li, Ke; Cheng, Dong-Ming; Li, Bo; Wang, Yong-Hui; Zang, Hong-Ying; Li, Yang-Guang
Graphical abstract: A novel polyoxometalate-based coordination supramolecule was synthesized via a hydrothermal method. The compound exhibited high proton conductivity with good stability. Polyoxometalate skeleton, 2-methylimidazole ligands and water molecules provided continuous hydrogen bonds for the proton conduction. Kinetic studies indicated that the proton conduction mechanism of the compound followed the vehicle mechanism. Abstract: Developing new low-cost and efficient proton-conducting materials remains an attractive and challenging task. Herein, a Preyssler-type polyoxometalate derived coordination compound had been synthesized with a hydrothermal method, namely, H4.5 NaCo5 (2-MI)15.5 (2-MI)3 [NaP5 W30 O110 ]·5H2 O (1 ) (where 2-methylimidazole is abbreviated as 2-MI, and partial 2-MI was deprotonated). The structure was characterized by single crystal X-ray diffraction, PXRD, FT-IR, TG, CHN and ICP-OES elemental analyses. We studied the relationship between the crystal structure and proton conduction of compound1 and found that the presence of 2-MI reduced the leakage of polyoxometalate under high relative humidity. Meanwhile, the strong interaction of the counter cation Na + with water is beneficial to form more hydrogen bonds. Compound1 showed the maximum proton conductivity with a value of 4.42 × 10 −3  S cm −1 at 367 K and 97% RH. Kinetic investigation indicates that the proton conduction mechanism of compound1 follows the vehicle mechanism.